IMPLEMENTASI METODE AMTSILATI DALAM MEMBACA KITAB KUNING DI PONDOK PESANTREN HIDAYATUL MUBTADIIN DEMAK - Wahyu Najib Fikri (POTENSIA: Jurnal Kependidikan Islam, 2018)
The method of amtsilati is a method or tool used in reading and understanding the yellow book, where the book is a programmed and systematic book as well as a new breakthrough in facilitating reading the yellow book. The purpose of this study is to describe the application of amtsilati method in reading the yellow book, advantages and disadvantages in using the method of amtsilati in Pondok Pesantren Hidayatul Mubtadiin Demak. This type of research uses descriptive qualitative research type with case study research method. The results showed that the method of amtsilati is a new method of breakthrough to facilitate reading the yellow book. The advantages of the amtsilati method of the book of amtsilati is a programmed and printed lesson with a systematic arrangement.